EMPLOYMENT, GENDER, EDUCATION AND OTHER RELEVANT VARIABLES: THE FINANCIAL CRISIS IMPACT IN SPAIN - Flora M. Diaz-Perez; Olga Gonzalez-Morales (European Regional Science Association (ERSA), 2011)
The present paper aims to ascertain whether gender differences continue to exist in Spain's working population. It sets out to obtain empirical evidence of the employment profile according to gender, quantify the extent to which self-employment or salaried employment is associated with certain characteristics (age, education, marital status and economic sector) and to analyse the evolution undergone during the recent economic crisis (2005-2009). In the study multivariate analysis statistical techniques will be applied to micro-data from the Working Population Survey compiled by Spain's National Statistics Office (INE). Results shows that significant gender differences in employment status are seen when this is disaggregated and that the economic crisis has had a negative impact especially in certain groups.
Keywords: 330